A sourcebook of HIV/AIDS prevention programs (World Bank, 2008)
A Sourcebook of HIV/AIDS Prevention Programs, Volume 2 aims to support efforts by countries to strengthen the role of the education sector in the prevention of HIV/AIDS. It was developed in response to numerous requests for a simple forum to help countries share their practical experiences of designing and implementing programs that are targeted at school-age children. The Sourcebook seeks to fulfill this role by providing concise summaries of programs, using a standard format that highlights its main elements for easier program comparison. The 2nd Edition documents 13 education based HIV/AIDS prevention programs targeting children and youth from 7 sub-Saharan African countries. The Sourcebook represents the work of many contributors, and was developed by the Partnership for Child Development with the World Bank. Its sponsors include UNAIDS, UNICEF, UNESCO, UNFPA, DFID, USAID, Ireland Aid and the World Bank.